Expeditionary police advising: some causes of failure. (2nd November 2018) - Stoker, Donald; Westermann, Edward B.
ABSTRACT: The practice of dispatching teams of police advisors to other states to build or train foreign security forces began at the end of the nineteenth century, yet there exists no definitive history of the practice, or any definitive theoretical approach underpinning why such missions succeed or fail. Drawing upon their recent edited book on expeditionary police advising, and by examining the donor or sending states, the host nations, and the use of police in counterinsurgency situations, the authors present some key reasons why such missions fail, and lay some groundwork for additional study of this important subject.